KEMAMPUAN MENENTUKAN FAKTA DAN OPINI DALAM TAJUK RENCANA DENGAN TEKNIK INKUIRI SISWA KELAS XI SMAN 1 SUNGAI RUMBAI KABUPATEN DHARMASRAYA - Wesni, Tita; Eska, Wirnita; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2014)
Background of this research are (1) the studentsâ are less interesting in reading, (2) the studentsâ are less creative in reading another texts, (3) the students have not prior knowledge about the fact and opinion, (4) the technique that the teacher used in reading are not interesting. The purpose of this research is describing the studentsâ ability to determine the fact and opinion in Editorial by using Inquiry technique at Eleventh grade of Senior High School 1 Sungai Rumbai, Dharmasraya. The design of this research is Descriptive Quantitative Research, where the research have to use numbering within collecting the data, analysing the data and the result of the data. The expected result of this research are (1) the studentsâ are able to determine the fact and opinion in Editorial by using Inquiry technique in qualification more than âenoughâ (73,55) with a value stretch 66-75%. (2) the studentsâ are able to determine the fact and opinion by using Inquiry technique in âgoodâ qualification (85-79) with a value stretch 76-85%. (3) the studentsâ are able to determine the fact and opinion in Editorial by using Inquiry technique at eleventh grade of Senior High School 1 Sungai Rumbai, Dharmasraya in âgoodâ qualification (82-55) with a value stretch 76-85%.